Speaking to Memory: Images and Voices from St. Michael’s Residential School. MUSEUM OF ANTHROPOLOGY, UNIVERSITY OF BRITISH COLUMBIA - Bushey, Jessica (Archivaria, 2014)
Speaking to Memory: Images and Voices from St. Michael’s Residential School. MUSEUM OF ANTHROPOLOGY, UNIVERSITY OF BRITISH COLUMBIA. Mounted at the O’Brian Gallery, Museum of Anthropology, University of British Columbia, Vancouver. 18 September 2013 to 11 May 2014. Curated by BILL McLENNAN, SARAH HOLLAND, and JUANITA JOHNSON.